Putting the spotlight on donation‐related risks and donor safety – are we succeeding in protecting donors?. Issue 3 (26th October 2020) - Mikkelsen, Christina; Mori, Gaia; van Walraven, Suzanna M.; Castrén, Johanna; Zahra, Sharon; MacLennan, Sheila; Seidel, Kirsten; Fontana, Stefano; Veropalumbo, Eva; Cannata, Livia; Pupella, Simonetta; Kvist, Maria; et al.
Abstract: Background and objective: The European consortium project TRANSPOSE (TRANSfusion and transplantation: PrOtection and SElection of donors) aimed to assess and evaluate the risks to donors of Substances of Human Origin (SoHO), and to identify gaps between current donor vigilance systems and perceived risks. Materials and methods: National and local data from participating organizations on serious and non‐serious adverse reactions in donors were collected from 2014 to 2017. Following this, a survey was performed among participants to identify risks not included in the data sets. Finally, participants rated the risks according to severity, level of evidence and prevalence. Results: Significant discrepancies between anticipated donor risks and the collected data were found. Furthermore, many participants reported that national data on adverse reactions in donors of stem cells, gametes, embryos and tissues were not routinely collected and/or available. Conclusions: These findings indicate that there is a need to further develop and standardize donor vigilance in Europe and to include long‐term risks to donors, which are currently underreported, ensuring donor health and securing the future supply of SoHO.